1999
DOI: 10.1111/j.1559-1816.1999.tb02301.x
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual Production and Achievement Orientation in Competitive Athletic Settings1

Abstract: Two studies examined the impact of achievement orientation on counterfactual production in competitive sporting situations. In Study 1, participants created counterfactuals after reading 4 vignettes. Results indicated that participants reading about winners created more subtractive and downward counterfactuals than did participants reading about losers, while participants reading about losers created more additive and upward counterfactuals than did participants reading about winners. In Study 2, using partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Third, our findings contribute to the study of the preparatory function of counterfactual thinking. They show that counterfactuals can have a preparative function also at the collective level, that is, when the actor and action involved are collective, extending previous findings on the preparative function of counterfactuals at the individual level (Boninger et al , 1994; Grieve et al , 1999; Haynes et al , 2007; Markman et al , 1993, 2009; Sanna et al , 2001).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Third, our findings contribute to the study of the preparatory function of counterfactual thinking. They show that counterfactuals can have a preparative function also at the collective level, that is, when the actor and action involved are collective, extending previous findings on the preparative function of counterfactuals at the individual level (Boninger et al , 1994; Grieve et al , 1999; Haynes et al , 2007; Markman et al , 1993, 2009; Sanna et al , 2001).…”
Section: Discussionsupporting
confidence: 82%
“…People with such a perspective are not prisoners of what might have been. Instead, they project themselves into the future and think about what might be done the next time to improve subsequent performance, so that upward counterfactuals are a first step towards self‐improvement and self‐protection (Boninger et al , 1994; Grieve, Houston, Dupuis, & Eddy, 1999; Haynes et al , 2007; Markman et al , 1993; Markman, Karadogan, Lindberg, & Zell, 2009; Sanna, Chang, & Meier, 2001). In other words, upward counterfactuals motivate people to try again in the future, because they indicate that, while past outcomes were negative, future outcomes may still improve (Johnson & Sherman, 1990; Sanna, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown upward counterfactuals to outnumber downward counterfactuals (Nasco & Marsh, 1999;Roese & Olson, 1997), and additive POLARISED COUNTERFACTUALS 5 counterfactuals to be more frequent than subtractive ones (Roese, Hur, & Pennington, 1999). Some studies indicate a positive relationship between these two dimensions, in the sense that additive counterfactuals typically describe situations that could have been better, whereas subtractive counterfactuals may more often be used to describe a downward comparison (Grieve, Houston, Dupuis & Eddy, 1999;Roese & Olson, 1997). In the present experiment we test this hypothesis without restricting participants to sample their thoughts from any specific domain.…”
Section: Methodsmentioning
confidence: 64%
“…When targeting the expression or suppression of various emotional symptoms it might be worthwhile implementing cognitive restructuring techniques that focus on changing the direction of person counterfactuals. In the context of professional sport, this 24 might involve the reassessment of personal goals or perceptions of outcome control (see Grieve, Houston, Dupuis, & Eddy, 1999). Although there is no guarantee that this will cause changes in emotional states (as our study did not address causality) the directionally hypothesised relationships outlined in psychological theory (e.g., Roese, 1997;Sanna et al, 2006) suggest this may be the case.…”
Section: Discussionmentioning
confidence: 88%